#TITLE_ALTERNATIVE# - Al Amin Najib - 13611051 , Noval
This thesis explores the methods necessary to modify an available XPlane10 aircraft model in the hopes of achieving an accurate overall performance, cruise lift over drag characteristic, as well as the pitching moment characteristics of an aircraft model in the XPlane10 simulator. The main idea of the method underwent in this thesis is by deciding several fixed parameters that are known to be accurate and the modification of several unknown variables to adjust the outcome of the simulations. The aircraft model this thesis is exploring is the Airbus A320-216 single aisle twin engine transport aircraft. The fixed parameters of the aircraft model in this thesis are the geometry of the main aircraft components to ensure a proper reference geometry, as well as the weight and balance parameters, such as the MTOW, empty weight, fuel load, CG range, fuel tank locations and volumes. The modifiable variables are the 2-D airfoil drag characteristics as well as the engine SFC. These values are modified according to latest outcome of the simulation and how they compare to the reference values. The final analysis suggests that the resulting aircraft model can only be used accurately and dependably in a very narrow range of cruise flight conditions. They are between the elevation of FL290 to FL350, with a total CL value of around 0.3, and a cruise duration of over one hour long. To improve the range of dependable flight condition, there should be more reference data to increase the number of fixed parameters as well as deciding more modifiable parameters to improve the fine-tuning of the outcome of the simulations.